A Study on English Students' Perception Regarding the AI Implementation on Listening and Speaking Skills - Azzahra, Naziha; Tri Widiastuti, Pina; Sopyani, Nopi; Luthfiyyah, Roghibatul; Dwiniasih (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2024)
Listening and speaking teaching have always been weak links in English teaching. The emergence of the intelligent learning system breaks the traditional learning method in the classroom, allowing students to obtain learning resources anytime, anywhere, free from fixed time and fixed space. This study aims to know student perceptions of English educational students regarding the implementation of AI to increase listening and speaking skills and to know the limitations and difficulties English education students face while using Duolingo and ELSA Speak applications. We conducted a reflection and semi-structured interview among undergraduate English education students in West Java. A total of 6 participants and all of them are 7th semester English Language Education students. The majority of them agree that AI can increase listening and speaking skills, especially Duolingo and ELSA Speak. Even though there are a lot of limitations and difficulties that need to be considered, such as having a stable internet connection and storage capacity, the student still mentioned that Duolingo and ELSA Speak are great applications for improving listening and speaking skills.